(untitled) (Economic and Political Thought, 2013)
The European Central Bank (ECB) is perhaps the only technocratic institution of the European Union, which gathers substantial authority during the crisis. It is also perceived as an institution, which successfully stabilizes the crisis in the euro area. The article is aimed at explaining the phenomenon of that bank during the crisis. First of all, the question whether the ECB activities are appropriately legitimized is answered. Does the crisis-based situation authorize the Bank to go beyond the treaty mandate? Is the ECB really efficient and does it improve its ‘utilitarian legitimization’? Does it remain a reliable institution, i.e. independent of the biggest states’ political influence? In addition, the author presents the Bank’s activities political repercussions for the formulation of the ‘technocratic quasi-federation’ that was under the strong informal influence of the biggest member states.